USE OF IFRS BY ENTITIES OF SMALL BUSINESSES: FEATURES OF IMPLEMENTATION AND PROBLEM ASPECTS - POLISHCHUK, Olena; BILOUS, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the use of IFRS by small business entities in Ukraine. Implementation of international financial reporting standards (IFRS) is a significant step on the way to harmonizing the domestic accounting system with international standards. This process should contribute to the improvement of the quality of financial reporting of enterprises, transparency of their activities and competitiveness on the world market. IFRS are global financial reporting standards designed to ensure comparability of financial reporting of enterprises in different countries. In the course of the work, the impact of IFRS on small business, the peculiarities of implementation of IFRS by small business entities were analyzed. The advantages and disadvantages of IFRS implementation by small business entities are determined. The advantages were attributed to: improving the quality of financial reporting, increasing the transparency and comparability of financial information, facilitating the company’s entry into international markets, establishing partnerships with foreign companies, attracting foreign investments and obtaining external loans. Among the disadvantages are the costs of implementing IFRS and increasing the complexity of accounting. It was established that the use of IFRS by small business entities is an important factor in increasing their financial stability and competitiveness. It has been proven that the implementation of IFRS by small business entities in Ukraine is accompanied by certain problems that are directly related to the specifics of the application of IFRS, as well as to other, both internal and external, challenges faced by enterprises at the moment, the main of which are: lack of awareness and qualification of accountants, financial difficulties, peculiarities of taxation. The directions for optimizing the implementation of IFRS by small business entities are presented, the problems that may arise in this case are identified, and the directions for their solution are proposed. Conclusions are drawn, directions for further research are suggested.